Arabic: Analysis of Core Competency Levels in the KMA No. 183, 2019 on the Arabic Language Curriculum for Elementary Level According to the CEFR - Nurcholis, Agung; Asrori, Imam; Shockley, Mark Daniel; Suryadarma, Yoke (University of Darussalam Gontor, 2024)
In case of rapid transformations and global needs, educational curriculum must adapt to these changes. Thus, the Ministry of Religious Affairs issued Decree KMA 183 of 2019, aimed at preparing students to understand Islamic principles and fostering Islamic culture, including the Arabic language. The researcher applied a descriptive content analysis method to investigate the implementation of KMA 183 of 2019 and assess it according to the Common European Framework of Reference for Languages (CEFR) standards in Arabic language education in Indonesia. This article analyzes the curriculum using the CEFR framework to determine Arabic language learning levels at the elementary level. The study found a positive alignment between the KMA 183 curriculum and CEFR standards, contributing to improved Arabic language education for non-native speakers and enhancing students' linguistic and cultural competencies. The researcher hopes that those responsible for Arabic language learning and teaching in Indonesian elementary schools will take this matter seriously, implementing the KMA 183 curriculum for Arabic education, as it aligns effectively with the established standard.